Synthesis and Characterization of Novel Basketing of C-4Phenylocta-phenylhydrazide-calix[4]resorcinarene-PdNPs - Busroni, Busroni; Handayani, Ari Tri Wanodyo; Irawan, Eka Deddy; Anwar, Chairil (AIP Conference Proceedings, 2022)
The novel synthesis basketing of C-4-phenylocta(phenylhydrazide)calix[4]resorcinarene-PdNPs/(K4ROPHPdNPs). The route have been synthesized target compounds, including: (1) C-4-phenyloctahydroxycalix[4]resorcinarene (K4R), (2) C-4-phenyloctahydroxycalix[4]resorcinarene-acetate, (3) C-4-phenyloctaphenylhydrazidecalix[4]resorcinareneamida (K4ROPH and (4) C-4- phenylocta(phenylhydrazide)calix[4]resorcinarene-PdNPs (K4ROPH-NPs). Compounds of K4ROPH-PdNPs were characterized carried out with FTIR, TEM, 'H-NMR (500 MHz, DMSO-d6), andUV-Visto determine ligands functional groups and particle size of ligands before and after being complexed with palladium transition metals. The results of particle size analysis using Transmission Electron Microscopy (TEM), obtained of K4ROPH-PdNPs have a particle size between 3-13 nm. © 2022 American Institute of Physics Inc.. All rights reserved.